Evaluation of the Implementation of the Free Health Check Program: Preparation, Challenges, and Impact on the Community - Irawan, Teguh; Indriani, Yulis; Maryam, Dwi Kafita; Sari, Diesta Ayu Permata; Nuraini, Ninu; Pangestu, Naufal Ilham; Dinov, Syamkhan Fatkhu; Khusna, Thifla Emila (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Infectious and non-communicable diseases remain a major cause of the global health burden, including in Indonesia. The government responded to this situation by launching a free health check-up program as an initial screening effort and to increase public health awareness. This study aimed to evaluate the implementation of the free health check-up program at the Warungasem Community Health Center through a qualitative approach using the CIPP framework, which encompasses Context, Input, Process, and Product. This research was conducted using a qualitative approach. Data were obtained through in-depth interviews with 12 informants representing program implementers and beneficiaries, and then analyzed narratively. The results indicate that the program has a clear goal of early detection and targets the entire life cycle. The availability of medical personnel and basic facilities supports implementation, although challenges remain, including limited advanced examination equipment and staff workload. Socialization through social media and directly at the community health center (Puskesmas) has helped disseminate information, but has not yet reached the entire community. Public awareness of the importance of health check-ups remains low. Evaluations are conducted routinely by the community health center and the health office, but participation rates have not yet reached the minimum target. Furthermore, it is concluded that the program has a positive impact on building understanding and healthy living behaviors.Keywords: free health check-up; evaluation; challenges; health center; screening